NAIAD-2020: Characteristics of Motor Evoked Potentials After 3-Day Exposure to Dry Immersion in Women - Nosikova, Inna; Riabova, Alexandra; Amirova, Liubov; Kitov, Vladimir; Tomilovskaya, Elena (Frontiers in Human Neuroscience, 2021)
As female astronauts participate in space flight more and more frequently, there is a demand for research on how the female body adapts to the microgravity environment. In particular, there is very little research on how the neuromuscular system reacts to gravitational unloading in women. We aimed to estimate changes in motor evoked potentials (MEPs) in the lower leg muscles in women after 3-day exposure to Dry Immersion (DI), which is one of the most widely used ground models of microgravity. Six healthy female volunteers (mean age 30.17 ± 5.5 years) with a natural menstrual cycle participated in this experiment. MEPs were recorded from the gastrocnemius and soleus muscles twice before DI, on the day of DI completion, and three days after DI, during the recovery period. To evoke motor responses, transcranial and trans-spinal magnetic stimulation was applied. We showed that changes in MEP characteristics after DI exposure were different depending on the stimulation site, but were similar for both muscles. For trans-spinal stimulation, MEP thresholds decreased compared to baseline values, and amplitudes, on the contrary, increased, resembling the phenomenon of hypogravitational hyperreflexia. This finding is in line with data observed in other experiments on both male and female participants. MEPs to transcranial stimulation had an opposing dynamic, which may have resulted from the small group size and large inter-subject variability, or from hormonal fluctuations during the menstrual cycle. Central motor conduction time remained unchanged, suggesting that pyramidal tract conductibility was not affected by DI exposure. More research is needed to explore the underlying mechanisms.